Pragmatic approach to construction and reinvention of cities in developing countries: the case of Brazzaville in the Republic of Congo - HILAIRE KEVIN, NZOUSSI (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
Urbanization is a very old phenomenon and does not date today. For centuries, the urbanization of cities has been inevitably accelerating. In recent years, more than 50% of the world's population lives in urban areas.This percentage will increase in the coming years. Urbanization poses many problems in the cities of developing countries that require reinvention and pragmatic constructions to achieve sustainable cities. This is the case of Congo Brazzaville capital policy that is growing disproportionately and disorderly without planning methods or urbanization or even adaptation to receive a large population who moved to town in search of well being. Urbanization is a perplexed area and includes several sub-issues that are: socio-economic, environmental but also spatial. However, Brazzaville is in a state of total disrepair resulting in a dysfunction of the urban space. Brazzaville has inherited a colonial space with a dual character. The pragmatic reconstruction will certainly provide an adequate response to the problems facing the city of Brazzaville. The purpose of this paper is to provide a framework for the regulation and regeneration of the urban environment. Then, rethinking renaming the city of Brazzaville to ensure a pragmatic reconstruction that will allow the populations to have a radiant living environment.